CHARACTER AND MORAL VALUE “IN THE SOUND OF MUSIC” BY ROBERT WISE - Aan Handayani; Gustaman Saragih (Universitas Indraprasta PGRI, 2020)
The research aims to analyze the characters and moral values contained in the film